Behavior of Simply Supported Reinforced Concrete Beam with Edge Opening with and without Repairing - Khalaf Mohaisen, Saad; Sabah Ahmed, Ali; Waleed Abass, Zena (Journal of Engineering and Sustainable Development, 2012)
This study is an attempt to find out how the reinforced concrete beams with edge openings behave under the effect of shear forces. Eight simply supported reinforced concrete beams were tested under two-point loads to measure the deflections, up to a specific limit that is below collapse. After that, the samples were repaired with steel plates of the thickness of 0.5mm with dimensions (120×30mm). These plates were stuck on the concrete beams using epoxy. The repaired beam was retested, measuring deflection versus loads up the appearance of the first crack. Three of these beam samples were strengthened by steel plates stuck to the faces of their opening. The dimensions of those plates were (150×100×0.5mm). All results were compared with the results obtained from ANSYS 7.0 program. It was found that the results were acceptable and could be adopted to give a good view of the behavior of such samples.